Groundwater quota versus tiered groundwater pricing: Two cases of groundwater management in north-west China - Eefje Aarnoudse; Wei Qu; Bettina Bluemling; Thomas Herzfeld (International Journal of Water Resources Development, 2017)
Difficulties in monitoring groundwater extraction cause groundwater regulations to fail worldwide. In two counties in north-west China local water authorities have installed smart card machines to monitor and regulate farmers' groundwater use. Data from a household survey and in-depth interviews are used to evaluate the effectiveness of the different regulatory institutions implemented with help of the smart card machines. In the given context, groundwater quota is more effective in curbing farmers' groundwater use than the tiered groundwater pricing. The study shows that the usefulness of smart card machines depends on their embedding in the societal context and related regulatory institutions.
Keywords: 330; groundwater regulation; tiered groundwater pricing; water policy reforms; smart card machines; China